Persepsi siswa tentang keselarasan profil lulusan dan kurikulum dalam pendidikan Bahasa Inggris - Dwi Adinda Puspitasari; Yuyun Yulia; Lusi Nurhayati (Curricula: Journal of Curriculum Development, 2026)
Curriculum alignment plays a crucial role in ensuring that learning outcomes are effectively achieved in higher education. This study aims to examine students’ perceptions and understanding of the graduate profile within the framework of curriculum alignment in an English Education program. The research is conducted to evaluate whether students not only perceive the curriculum as relevant but also fully understand the intended graduate competencies. A quantitative approach, supported by open-ended responses, was employed to analyze students’ perceptions and level of understanding. The findings reveal that the majority of students hold positive perceptions of the graduate profile, while their understanding remains relatively low. This indicates a gap between students’ affective perceptions and their cognitive comprehension of curriculum objectives. In addition, students are more familiar with the role of a novice teacher than with those of a researcher and an edupreneur, reflecting an imbalance in the emphasis on competencies. These findings suggest that although the curriculum is perceived as relevant, its intended outcomes are not fully internalized.